Análise de custos dos serviços de coleta e disposição de resíduos sólidos domiciliares (RSD) como subsídio para elaboração de sistema de tributação no município de Jaboticabal - SP - Gracioli, Grazielli Padilha (2005)
The Domestic Solid Residues (DSR) have been discussed thoroughly on the part of The Public Power and the civil society, before the demands of the implantation of sanitary embankments, the construction of separating composting, selective collects, action of street and sanitary embankments workers, the formation of work cooperatives, collection forms and payment of the services, among others. This last subject, which sends to taxation forms and financing the activities of the system of solid residues, has not still been approached sufficiently in research terms, above all in municipal districts of small and medium load. Because of it, this work search intends to analyze the services related to RSD rendered by the municipal administration, through the identification of the equipments and people involved, as well as the operational and administrative costs, in the routes and collection ways (selective and pattern), of the amount of residues and disposition places. For that it was made the characterization of the activities related to DSR based in the structure, collection system and disposition, through data collected in the municipal administration. It was observed that the total cost of the collection of residues is distributed in 69,6% personal total and 30,4% representing the equipment total, maintenance, fuel and capital costs, totaling the worn-out value for the Municipal City Hall of Jaboticabal in the collection services and disposition of the urban solid residues. Analyzing the amount of urban homes in the municipal district and the values attributed in the costs of the collection services and disposition of the residues urban home solid is verified an annual medium cost by home in the order of R$ 72,00 (seventy two real). Taking as study object the municipal district of Jaboticabal - SP was made a characterization in neighborhoods, diagnosing the volume, type and pattern of residues of the selected properties. The characterization and differentiation of the general profile of the three selected neighborhoods were made, through the descriptive analysis and for the processing of statistical analysis techniques, using of variables: socioeconomic, generation of home solid residues and the consumption of water. Comparing the medium consumption of water in the researched residences, with the socioeconomic profile and the generation of home solid residues, was noticed that the pattern of consumption of residues, the income " per captures " of each neighborhood and the medium consumption of water: 40,05 m³/water (Nova Jaboticabal neighborhood), 27,17 m³/water (Aparecida neighborhood) and 16,54 m³/water (Conjunto Habitacional Ulisses Guimarães) are directly correlated. After characterizing the service of collection of the home residues and trace the general profile of the neighborhoods they were correlated and analyzed, together the 9 selected variables, through statistical analysis (main components, grouping, factorial and discriminant) looking for the elaboration of an exploratory model of taxation that is taken in consideration the socioeconomic profile, consumption of water and generation of the residues of the homes involved. The technique of grouping analysis divided the homes in three groups in agreement with the similarity of acting of the used variables, so that those homes that presented close actings were in the same group. Two variables identified as significant, being the Family Income and IPTU. So it can be said that with the values of IPTU and Family Income applied to the model it is gotten to identify what group belongs the analyzed home contributing like this in the taxation process, because the same ones can aid in the base of calculation of the municipal district through an exploratory model.